BBC Micro:bit in practice a hands-on guide to building creative real-life projects with MicroPython and the BBC Micro:bit - Pajankar, Ashwin; Sharma, Abhishek; Saini, Sandeep (PACKT PUBLISHING LIMITED, 2022)
Develop real-world interactive physical computing applications using the Micro:bit with more than 100 MicroPython examples with circuit diagrams Key Features Explore hardware programming and leverage the power of the BBC Micro:bit and MicroPython Build real-life creative projects step by step with each chapter increasing in complexity and interactivity Learn the features of the Micro:bit and how to interface it with electronic components through circuits and code examples Book Description This book is a one-stop guide for learning BBC Micro:bit with MicroPython, exploring many hardware components and programming techniques to provide detailed insights into developing practical applications with the Micro:bit. It will also show you how hardware components can be manipulated using a combination of Micro:bit and MicroPython for developing practical projects. BBC Micro:bit in Practice will help you gain a holistic understanding of the BBC Micro:bit platform and MicroPython programming, guiding you through mini projects aimed at developing practical knowledge of circuit design and writing programs. You'll learn how to write programs for working with built-in LEDs and buttons, interfacing external LEDs, buttons, motors, buzzers, and much more. You'll also work with built-in radio, speakers, accelerometer, and a compass. You'll dive into concepts related to the Micro:bit filesystem, interfacing external displays, and working with libraries in detail before exploring sewable circuits and wearable technology. After reading this Micro:bit book, you'll understand how to apply principles in electronics and MicroPython to create interesting real-life projects from scratch. What you will learn Explore the essentials of the BBC Micro:bit, its hardware specifications, and versions Program built-in and external LEDs and buttons Program external LED-based displays, buzzers, and stepper motors Use analog input and pulse width modulation to drive a servo motor Detect gestures with internal sensors such as accelerometer, compass, and magnetometer Work on projects with built-in features such as music, speech, radio, and filesystem Explore the advanced features of the Micro:bit Who this book is for This book is for anyone who wants to use the combination of MicroPython and the BBC Micro:bit for building exciting real-life projects. Engineers, researchers, hobbyists, and technology instructors working in areas such as embedded systems, electronics, software development, IoT, robotics, teaching, and training will find this book useful for building projects. Prior experience with building basic electronic circuits and any programming language, not necessarily MicroPython, will be helpful.